(untitled) (Agro Productividad, 2026)
Objective: To determine the maximum dry matter production of Mexican needlegrass (Amelichloa clandestina) following an initial grazing with high stocking density and to provide recommendations for subsequent utilization. Design/Methodology/Approach: The growth rate (kg DM ha⁻¹ day⁻¹), morphological components, leaf-to-stem ratio, and plant height of Mexican needlegrass (Amelichloa clandestina) were evaluated through monthly sampling over an 18-month period. A randomized block design with three replications was employed. Results: Statistically significant differences were observed between regrowth months. The highest dry matter accumulation occurred in winter at 16 months, with a growth rate of 4.2 kg DM ha⁻¹ day⁻¹, a maximum plant height of 22 cm, and a leaf yield of 2.3 kg DM ha⁻¹ day⁻¹. In contrast, spring showed greater productivity, with peak dry matter production recorded at 14 months (8.4 kg DM ha⁻¹ day⁻¹), reaching a maximum height of 43 cm at 18 months. The leaf-to-stem ratio in spring was 4.0, compared to 7.2 in winter. Limitations/Implications: The results may be affected by local environmental conditions specific to the region, which could limit generalization to other geographic areas. Findings/Conclusions: A second grazing can be scheduled fewer than six months after the initial regrowth of Amelichloa clandestina in southeastern Coahuila, Mexico, especially when grazed under high stocking density in early spring. This is due to the higher growth rate observed in spring compared to winter.